(untitled) (Development Service Industry Management, 2024)
The article draws attention to challenges and threats to the stable functioning and development of enterprises in conditions of instability, caused in particular by the negative consequences of a full-scale war. The purpose of the article is to identify the challenges and justify the imperative of managing the economic security of enterprises in crisis conditions. The content characteristic of the concept of economic security of the enterprise has been specified. The challenges of ensuring the economic security of enterprises in conditions of crisis, in particular full-scale war, have been identified. The imperatives of managing the economic security of enterprises in crisis conditions are determined. Measures and means have been developed, the implementation of which is aimed at guaranteeing the economic security of the enterprise in conditions of instability. Reference points are indicated, which should be followed by business entities in order to strengthen their economic security in crisis conditions. It was established that in the conditions of a crisis caused by a full-scale war, new systemic challenges affected all without excluding the main components of the economic security of domestic enterprises, in particular, financial, intellectual-personnel, technical-technological, product, information, power, etc. The following were the most significant challenges: decrease in income, profit and deterioration of the financial result; increase in consumption; population migration and loss of personnel; staff mobilization; weakening of personnel resources; decreasing attention to innovative technologies; increase in value, respectively, the price of products; the growth of cyber security threats; spread of fakes; military risks of loss of property and personnel. It is justified that in such new realities, enterprises should improve their own systems for ensuring economic security. Corresponding measures should be formed according to the specified components of security and should be aimed at overcoming the identified new challenges and threats that have become actualized in conditions of instability. It has been proven that it is expedient to determine the imperatives of management improvement policy in the field of economic security of domestic enterprises: diversification of activities; vertical and/or horizontal integration; automation and digitization of business processes; preservation of strategic personnel and improvement of their training system; application of remote forms of employment; development of digital communications tools; improvement of marketing tools; improvement of cyber security systems.